Antara Islam dan Hinduisme di Alam Melayu: Beberapa catatan pengkaji barat - Mohd. Zariat Abdul Rani, (Universiti Kebangsaan Malaysia, 2005)
This article is inspired by Syed Muhammad Naquib Al-Attas’s notion on Westerners’ inclinations of their observation of the Malay World. In this context, Al-Attas claims that a majority of Western researchers tend to take for granted the role of Islam. In contrast, they seem to recognize the significant influence of Hinduism in the Malay history and culture. Taking into consideration of Al-Attas’s notion, this article attempts to observe the viewpoints of three Western researchers: N. J. Krom (1950) in De Hindoe-Javaansche Tijd; Bernard H. M. Vlekke (1959) in Nusantara: A History of Indonesia; and J. C. Van Leur (1955) in Indonesia: Trade and Society. Observation on these writings reveals a pattern of inclination in presenting Hinduism as a dominant influence to the Malay culture. This inclination also explains the stance of these writings on Islam, which could not compete with the prominent influence of Hinduism in the Malay World